Carrying Capacity Analysis for Measuring Land Capability in Arid Area - Asep Saepulloh; Maria Dolorosa Bhebhe; Aang Anggara (Sriwijaya Journal of Environment)
The study of sustainable development in an area must include environmental carrying capacity (ECC). Measurement of environmental carrying capacity is needed to determine the limits of an area's ability to support individual behavior, such as consumption of natural resources and disposal of waste into nature. This study aims to evaluate the ECC analysis based on land capability in dry areas in East Nusa Tenggara as a contribution to spatial planning strategies. The results of this study show that Timor Tengah Selatan Regency, which is dominated by dry areas, has a land capability classification ranging from class I to III, or as much as 42% of the total area that can be exploited for agricultural and plantation activities. This research can be used as input for the 5-year revision cycle of the Timor Tengah Selatan Regency spatial plan so that land allocation in the RTRW is more in line with the land's carrying capacity.